Trumpets in the Mountains : Theater and the Politics of National Culture in Cuba - Frederik, Laurie Aleen (Book collections on Project MUSE., 2012)
An ethnography exploring how the meaning of cubanía, or Cubanness, is generated in interactions between the state, ordinary Cubans, intellectuals, and artists and other cultural workers.